2010
DOI: 10.1590/s0103-21002010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Questionário multidimensional para análise da imagem do enfermeiro

Abstract: RESUMOObjetivo: Construir um questionário multidimensional para avaliar a percepção de alunos do ensino médio frente sobre a enfermagem e validar o questionário multidimensional em conteúdo, aparência e análise semântica. Métodos: Estudo quanti-qualitativo com fins de instrumentação, utilizando o referencial teórico-metodológico de Pasquali, Silva e Ribeiro-Filho que recomendam as etapas de levantamento do conceito do constructo, geração dos itens do instrumento fundamentado na literatura e aferição das propri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
1
0
0
2
Order By: Relevance
“…The social devaluation of nursing is one of the main consequences of these stereotyped and prejudiced representations, so much so that, in a survey conducted with 269 high school students from São Paulo, a Multidimensional Questionnaire on the Social Image of Nurses (Questionário Multidimensional Sobre a Imagem Social do Enfermeiro, QMISE) was applied and, eventually, it was found that more than 70% of the sample did not consider nursing as a career to be followed. 16 In line with this study, even though it was found that nursing, predominantly, is not highlighted in the health series, this generates many reflections in the interviewees.…”
Section: /13supporting
confidence: 58%
“…The social devaluation of nursing is one of the main consequences of these stereotyped and prejudiced representations, so much so that, in a survey conducted with 269 high school students from São Paulo, a Multidimensional Questionnaire on the Social Image of Nurses (Questionário Multidimensional Sobre a Imagem Social do Enfermeiro, QMISE) was applied and, eventually, it was found that more than 70% of the sample did not consider nursing as a career to be followed. 16 In line with this study, even though it was found that nursing, predominantly, is not highlighted in the health series, this generates many reflections in the interviewees.…”
Section: /13supporting
confidence: 58%
“…Por outro, está reduzido à concepção histórica do cuidado caritativo, vocacional e não profissional. Considerando que a formação da identidade profissional se faz por diferentes aspectos (autoimagem, heteroimagem e imagem da realidade), a imagem pessoal do enfermeiro é influenciada pela forma como ele percebe seu papel social e profissional, além de sua satisfação com o trabalho e imagem corporal (14)(15)(16) .…”
Section: Artigo 16unclassified
“…Uma estratégia para favorecer a visibilidade da profissão é o uso do marketing pessoal, com o propósito da "venda" de sua própria imagem de forma positiva, de acordo com as necessidades de seus clientes, da rede de relacionamento e das oportunidades do mercado (13)(14)(15)(16) .…”
Section: Artigo 16unclassified